Atlas of prostate cancer heritability in European and African-American men pinpoints tissue-specific regulation - Alexander Gusev (Nature Portfolio, 2016)
Over one hundred loci have been identified to be associated with the familial risk of prostate cancer but the functional effects are poorly understood. Here the authors use single-nucleotide variant and epigentic data to show an underlying genetic architecture marked by histone modification.